Hemodynamic effects of prophylactic amiodarone assessed by pressure–volume analysis in anesthetized female pigs in sinus rhythm—An exploratory study - Laura Svanekjær; Emma Illum; Peter H. Frederiksen; Louise Linde; Anika Klein; Karoline Korsholm Jeppesen; Ann Banke; Sarah Holle; Lisette O. Jensen; Henrik Schmidt; Jens F. Lassen; Jacob E. Møller; et al. (PLoS ONE, 2026)
Background Intravenous amiodarone is used for acute management of severe arrhythmias and can cause hypotension. However, amiodarone’s direct hemodynamic and myocardial effects during sinus rhythm are not well characterized. Methods Twenty-five anesthetized female pigs (75–80 kg) received a 300 mg intravenous bolus amiodarone over 30 minutes. To assess hemodynamic effects, animals were instrumented with a left ventricular conductance catheter, a pulmonary artery catheter, a carotid artery Doppler flow probe, and a renal vein catheter. Data were recorded at baseline, after 15 and 30 minutes and presented as median with interquartile ranges. Results Amiodarone reduced systolic and mean arterial blood pressure by 12% (p < 0.001) after 30 minutes infusion, primarily driven by 24% reduction in cardiac output due to combined deceased heart rate (87 (79; 99) beats per minute (bpm) to 72 (62; 81) bpm, p < 0.001) and stroke volume (69 (64; 79) mL to 64 (48; 73) mL, p = 0.004). End-systolic elastance (EES) decreased (0.54 (0.33; 0.63) mmHg/mL to 0.43 (0.29; 0.51) mmHg/mL, p < 0.001), while systemic vascular resistance and arterial elastance (EA) remained unchanged, resulting in an increased EA/EES ratio from 2.45 (2.01;3.53) to 3.26 (2.55; 4.30) (p < 0.001). This impaired cardiac function led to reduced carotid artery blood flow and renal perfusion pressure. Conclusion Infusion of 300 mg amiodarone intravenously in anesthetized pigs in sinus rhythm impaired left ventricular contractility and caused ventriculo-arterial decoupling with increased EA/EES ratio. This led to reduced cardiac output, blood pressure, and reduced carotid- and renal blood flow.